Analysis of The Implementation of Early Discharge Planning at X General Hospital - Jesslyn Valentina; Dumilah Ayuningtyas (Green Publisher Indonesia, 2025)
The process of treating patients in hospitals generally takes a long time and costs a lot. This can cause various problems, such as overcrowding of inpatient rooms, long queues of patients, and increased health care costs. Early discharge planning (EDP) is a strategy that can be used to reduce the length of patient care and health care costs. The aim of this research is to analyze the EDP implementation process at X General Hospital from March-May 2024. This research method uses descriptive research methods. Data collection techniques in this research are observation, interviews and literature study. The data that has been collected is then analyzed using the univariate method with the help of a fishbone diagram. The research results show that X General Hospital faces a number of challenges in implementing the H-1 discharge planning strategy. Some of the problems identified include lack of uniformity of understanding among doctors in charge of patients (DPJP) regarding the H-1 discharge planning program, lack of DPJP participation in socializing the program, lack of communication standards between patient care officers (PPA) regarding the H-1 discharge planning program to patients and their families, the absence of a policy regarding compensation fees for DPJP on the day the patient is discharged if no visit is made, lack of standardization in communication regarding patient discharge, as well as less than optimal coordination between PPA via telephone or WhatsApp, and also a lack of effective coordination with third parties or guarantors via telephone or email.